Question
24. [-/2 Points] DETAILS MY NOTES SCALCET9 2.8.053. Use the definition of derivative to find \( f^{\prime}(x) \) and \( f^{\prime \prime}(x) \). \( f^{\prime}(x)=\square(x)=4 x^{2}+3 x+2 \) \( f^{\prime \prime}(x)=\square \) Need Help? Read It पatch it
Ask by Boyd Sandoval. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\[ f''(x) = 8x + 3 \]
Solution
Sure, let's find the first and second derivatives of the function \( f(x) \) using the definition of the derivative.
### Given:
\[ f'(x) = 4x^{2} + 3x + 2 \]
### 1. Finding the Second Derivative \( f''(x) \)
The second derivative \( f''(x) \) is simply the derivative of the first derivative \( f'(x) \).
Let's differentiate \( f'(x) \) with respect to \( x \):
\[ f''(x) = \frac{d}{dx} [4x^{2} + 3x + 2] \]
Differentiate each term separately:
- The derivative of \( 4x^{2} \) is \( 8x \).
- The derivative of \( 3x \) is \( 3 \).
- The derivative of the constant \( 2 \) is \( 0 \) (since constants do not change).
So, combining these results:
\[ f''(x) = 8x + 3 \]
### Summary:
- **First Derivative:**
\[ f'(x) = 4x^{2} + 3x + 2 \]
- **Second Derivative:**
\[ f''(x) = 8x + 3 \]
If you need to derive \( f'(x) \) using the definition of the derivative, here's a brief overview:
### Using the Definition of the Derivative to Find \( f'(x) \)
The definition of the derivative is:
\[ f'(x) = \lim_{h \to 0} \frac{f(x + h) - f(x)}{h} \]
Assuming \( f'(x) = 4x^{2} + 3x + 2 \) was obtained using this definition, then the second derivative follows as we've calculated above.
If you have the original function \( f(x) \) and need to find \( f'(x) \) from scratch, please provide \( f(x) \), and I can guide you through the process!
---
**Final Answers:**
\[ f'(x) = 4x^{2} + 3x + 2 \]
\[ f''(x) = 8x + 3 \]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Bonus Knowledge
To find the first derivative \( f^{\prime}(x) \) using the definition of the derivative, recall that it can be expressed as: \[ f^{\prime}(x) = \lim_{h \to 0} \frac{f(x+h) - f(x)}{h} \] If \( f(x) = \frac{4}{3}x^3 + \frac{3}{2}x^2 + 2x + C \), applying the limit shows that \( f^{\prime}(x) = 4x^2 + 3x + 2 \) matches your function perfectly! Now for the second derivative \( f^{\prime \prime}(x) \), simply differentiate the first derivative again: \[ f^{\prime \prime}(x) = 8x + 3 \] And there you have it! Now you know how derivatives build on each other like building blocks!